Impression Materials and Techniques Used in Fabrication of Complete Denture, Fixed Partial Denture and Dental Implants: A Questionnaire Survey - Maharjan, Anjana; K.C., Neela; Thapa, Sujan; Shrestha, Dipankar; Sharma, Rinu (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: Dental impression is a negative imprint of intraoral structures that is to be used for production of dental prosthesis. There are various materials like irreversible hydrocolloid, polyvinylsiloxane and polyether for making impression in complete denture, fixed partial denture and dental implants. Various techniques of impression making are used in above listed parts of prosthodontics. The aim of our research is to know commonly practiced materials and impression techniques in prosthodontics by registered dental practitioners of Nepal. Methods: A descriptive cross- sectional online study with census sampling technique was done in Patan Academy of Health Sciences from November – December 2024 after ethical approval from institutional review committee. Standard google questionnaire form was distributed through various web links and 251 respondents agreed to participate. Closed ended anonymous questionnaire consisted of three sections which included questions regarding techniques and materials used in fixed partial denture, complete denture, and dental implants respectively. Collected data from google form was received from participants and descriptive statistical analysis was performed for frequency and percentage of various type of materials and techniques used. Results: Out of 251 respondents, 76.9% of them were practicing FPDs, among them 73% were using stock tray, 19.9% were using custom tray impression technique and 7.1% were using digital impression. 65.3% of respondents were practicing complete denture, 61.5% were using alginate for primary impression and 72.3% were using zinc oxide eugenol for final impression and 96.9% of respondents were using green stick for border molding. Dental implants were practiced by 41.4% of respondents, among them 61.7% were using open tray technique and majority of respondents 84.5% were using poly vinyl siloxane for impression. Conclusion: There is rise in popularity of digital impression however the habit of conventional impression material and techniques have not faded out as maximum number of our study population are using conventional impression materials and techniques in various part of prosthodontics like complete denture, fixed partial denture, and dental implants.